2016
DOI: 10.1186/s12933-016-0453-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of perioperative insulin treatment on cardiodepression in mild adiposity in mice

Abstract: BackgroundWhile most studies focus on cardiovascular morbidity following anesthesia and surgery in excessive obesity, it is unknown whether these intraoperative cardiovascular alterations also occur in milder forms of adiposity without type 2 diabetes and if insulin is a possible treatment to improve intraoperative myocardial performance. In this experimental study we investigated whether mild adiposity without metabolic alterations is already associated with cardiometabolic dysfunction during anesthesia, mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Hyperglycemia is associated with a spectrum of poor outcomes including poor graft survival [14] and in animal studies is associated with defective handling of calcium in cardiac myocytes resulting in poor cardiac function [15]. Insulin treatment appears to reduce afterload and improve ventricular relaxation although changes in myocardial perfusion or contractility have not been demonstrated [16]. Treatment of hyperglycemia, especially in patients with non-insulin dependent DM, has been shown to improve immune function, hypercoagulability and possibly reduce the risk of infectious complications [1]; it is postulated that hyperglycemia results in impaired phagocytosis secondary to high intra-cellular calcium concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycemia is associated with a spectrum of poor outcomes including poor graft survival [14] and in animal studies is associated with defective handling of calcium in cardiac myocytes resulting in poor cardiac function [15]. Insulin treatment appears to reduce afterload and improve ventricular relaxation although changes in myocardial perfusion or contractility have not been demonstrated [16]. Treatment of hyperglycemia, especially in patients with non-insulin dependent DM, has been shown to improve immune function, hypercoagulability and possibly reduce the risk of infectious complications [1]; it is postulated that hyperglycemia results in impaired phagocytosis secondary to high intra-cellular calcium concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether hyperinsulinemia play a role in diabetic cardiomyopathy and heart failure is not well established. Previous studies have shown a direct relationship between insulin signaling and cardiac contractility [31]. The newly characterized InsR and β 2 AR complex in myocardium brings new prospects to the issue [3234].…”
Section: Hyperinsulinemia Promotes Desensitization Of Cardiac βArmentioning
confidence: 99%
“…Contrast-enhanced echography (CEUS) was performed as previous described [23][24][25] with a Vevo 2100 Imaging System and MS 250 Nonlinear Contrast Imaging transducer (VisualSonics Inc, Toronto, Canada). Microbubbles were prepared from perfluorobutane gas and stabilized with a monolayer of distearoyl phosphatidylcholine and polyoxyethylene (PEG) stearate.…”
Section: Renal Perfusion With Contrast Echographymentioning
confidence: 99%